Efektivitas Tahapan Pengelolaan Keuangan Terhadap Pembangunan Desa Di Desa Kauditan Satu Kecamatan Kauditan Kabupaten Minahasa Utara - Dotulong, Veronica G. F.; Pangemanan, Lyndon Reindhart Jacob; Sondakh, Mex Frans Lodwyk (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
This study aims to determine the effectiveness of village financial management stages for village development in Kauditan Satu Village, Kauditan District, North Minahasa Regency. This research was conducted for 3 months, from May to July 2023. The data used are primary data and secondary data. The sampling method used Purposive Sampling and Accidental Sampling with a sample of 30 respondents. The variable being measured is village financial management based on Law no. 6 Year 20 14, namely the stages of planning, implementation and supervision as well as analysis of financial ratios. The data analysis method used in this study is qualitative and quantitative. The research results obtained show the stages of village financial management towards village development in Kauditan Satu Village, Kauditan District, North Minahasa Regency based on village financial management based on Law Number 6 of 2014 starting from the planning stage, the implementation stage up to the monitoring stage can be said to have been effective , So that with the effective stages of financial management the calculation of the effectiveness ratio is said to have been effective in managing the Village Revenue and Expenditure Budget (APBDes) for village development by producing an average from 2018-2022 of 100%.